2018
DOI: 10.1108/caer-03-2018-0056
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the functional efficiency of agricultural futures markets in China

Abstract: Purpose The purpose of this paper is to quantitatively analyse the changes in the functional efficiency of the six Chinese agricultural futures markets and compare the relative behaviour of different futures markets. In addition, this paper analyses the causes of differences in the functional efficiency of agricultural futures markets and advances policy suggestions. Design/methodology/approach The method used in this paper is the social loss index proposed by Stein (1981, 1986). This method can quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In summary, the results indicated that corn futures prices had lead power and wheat futures prices had no lead power, which is the same as the results reported by Ronghua and Zhiling (2019). Additionally, soybean futures prices had leading power, and the lead power of the soybean futures price was stronger than that of corn futures prices.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In summary, the results indicated that corn futures prices had lead power and wheat futures prices had no lead power, which is the same as the results reported by Ronghua and Zhiling (2019). Additionally, soybean futures prices had leading power, and the lead power of the soybean futures price was stronger than that of corn futures prices.…”
Section: Discussionsupporting
confidence: 81%
“…Yang and Zhang (2013) found that soybean futures prices predicted more than 70% of its spot price movements. However, Ronghua and Zhiling (2019) identified that the corn futures market showed this leading role, but the wheat market did not.…”
mentioning
confidence: 99%
“…Judging from market activity and price fluctuations, China's futures market does not appear to be overreacted to information (LIU et al, 2020). Affected by factors such as spot market dependence, contract maturity, and trading activity, China's corn and soybean futures markets are the most efficient, while the wheat futures market is relatively inefficient (JU & YANG, 2018).…”
Section: Weak Form Efficiency Of Futures Marketmentioning
confidence: 99%
“…Empirical studies have examined the functional efficiency of Chinese agricultural futures markets (Demir et al., 2019; Ju & Yang, 2019; Li & Xiong, 2021; Liu et al., 2020). However, these studies focus on only one or two aspects of market quality, price discovery and hedging effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%